2020
DOI: 10.21203/rs.3.rs-29004/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SKP1 promotes YAP-mediated colorectal cancer stemness via suppressing RASSF1

Abstract: Background: Cancer stem cells have been recognized as an important drug target, however, the mechanisms underlying the maintenance of cancer stem cells have not been fully understood. SKP1 is a traditional drug target for cancer therapy, while, whether SKP1 could be a target for eradicating cancer stem cells remains elusive.Methods: Human colorectal cancer cell lines HCT-116 and HT-29 and primary human colorectal cancer cells were used in this study. Gene manipulation was performed by lentivirus system. The mR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…The depletion of CRB3 could regulate hippo pathway and lead to increased nuclear localization of YAP/TAZ [30,31,42]. The hippo pathway plays a crucial role in regulating the CRC progression [43][44][45][46]. In present study, we found that CRB3 knockdown inhibited Hippo pathway, and increased nuclear localization of YAP, suggesting that CRB3 regulated the CRC progression by Hippo pathway.…”
Section: Discussionsupporting
confidence: 55%
“…The depletion of CRB3 could regulate hippo pathway and lead to increased nuclear localization of YAP/TAZ [30,31,42]. The hippo pathway plays a crucial role in regulating the CRC progression [43][44][45][46]. In present study, we found that CRB3 knockdown inhibited Hippo pathway, and increased nuclear localization of YAP, suggesting that CRB3 regulated the CRC progression by Hippo pathway.…”
Section: Discussionsupporting
confidence: 55%